Crohn’s Disease - Meducator, The; Deng, Florence; Khattra, Ruhani (The Meducator, 2025)
Crohn’s disease (CD) is a chronic inflammatory disease of the gastrointestinal (GI) tract that falls under the umbrella of inflammatory bowel disease (IBD). A 2023 impact report estimated that approximately 4.1 in 1000 Canadians live with CD. CD is characterized by discontinuous and patchy ‘skip lesions’ and transmural inflammation. The former may impact any part of the GI tract from the mouth to the anus, while the latter extends across the entire thickness of the bowel wall. Symptoms are variable and may include diarrhea, abdominal pain, and weight loss, among other potential complications. Patients with CD experience a poorer quality of life due to unpredictable bouts of remission, relapse, and no known cure.